Serum Leptin as a Marker for Severity of Endometriosis - Shatha Sami Hussein; Fatin Shallal Farhan; Alaa Ibrahim Ali (Obstetrics and Gynecology International)
Background. Endometriosis a disease of theories, and one of the important causes of chronic pelvic pain, dysmenorrhea, dyspareunia, and subfertility. Surgery is the mainstay step for the diagnosis; noninvasive test is the goal in the future. Aim of Study. To test the role of serum leptin in determination of severity of endometriosis. Study Design. A cross-sectional study done in Al-Yarmouk Teaching Hospital from 1st of January 2018 to 1st of January 2019. Methods. 60 BMI-matched patients were involved in the study. A study group of 30 patients were operated either by laparoscopy or laparotomy for many reasons diagnosed as endometriosis by histopathology, and 30 normal women as a control group underwent elective surgery. Blood sample was taken from all patients in the theater room when laparoscopy finding went with endometriosis, and classifying according to surgical staging of endometriosis, the level of serum leptin was measured by ELISA using Human LEP (Leptin) ELISA Kit. The recording of finding of laparoscopy after conforming of diagnosis by histopathology was compared with the result of serum leptin. Result. The result shows no significant difference between the two groups regarding parity and age; however, the level of serum leptin was significantly high in the endometriosis group than in the control group. The P value was less than 0.05. Also, the result shows no significant differences between serum leptin in both groups according to the symptom but there was a significant difference with surgical staging. The mean of the level of serum leptin in stage 1 was 214.8, while it was 340.3 in stage 4. Conclusion. Serum leptin can be used as a marker of severity of endometriosis.